Review on Chemistry of Oxazole derivatives: Current to Future Therapeutic Prospective. Issue 1 (31st December 2023) - Joshi, Sweta; Mehra, Meenakshi; Singh, Ramandeep; Kakar, Satinder
ABSTRACT: Oxazole and its derivatives play a very essential role in the area of medicinal chemistry. Oxazole nucleus is heterocyclic five-membered ring that seemed to be investigated in the advancement of novel compounds which shows favorable biological activities. In the modern medicinal chemistry scaffold of oxazole has been intermittently satisfied as a functional lead molecule. Prominently, enormous oxazole candidates or drugs are developed for the treatment of disease which increases its developmental values as medicinal agents. The five-membered aromatic ring of oxazole has atoms of nitrogen and oxygen. Through diverse non-covalent bonds, these rings quickly engage physiologically with many enzymes and receptors, resulting in a variety of biological actions. This review presents a logical attempt toward the researches and advancement of chemistry and oxazole derivatives' biological action. The important information presented in this manuscript will work as impetus for new views in the pursuit for rational design of more biologically active and minimum toxic derivatives of oxazoles as medicinal agents. Graphical abstract: uf0001